Pengaruh Persepsi Pelanggan atas Kualitas Sistem Informasi Akuntansi, Harga, Promosi dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Pengguna Jasa Aplikasi GoFood (Studi Kasus Bagi Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Sur - Ikke Nur Ayyatusyifa Lismiawan; Lintang Kurniawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of customer perceptions of the quality of accounting information systems, prices, promotions and service quality on customer satisfaction in GoFood Application service users. The sampling technique used in this study was purposive sampling. A total of 100 respondents have met the criteria for filling out the questionnaire. The analysis method used is multiple linear regression analysis. The results of this study provide relevant evidence that the quality of accounting information systems, prices, and promotions do not affect customer satisfaction. While service quality affects customer satisfaction.